Hubungan antara Persepsi Situasi Pembelajaran dengan Pendekatan Belajar Mahasiswa Blok Muskuloskeletal di Fakultas Kedokteran Universitas Pelita Harapan - Rhendy Wijayanto; Harsono Mardiwiyoto; Amitya Kumara (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2012)
Background: Comprehension on student’s learning approach is an essential issue because it deals with the learning quality. Student’s perception on learning environment is a factor that influences student’s learning approach. The aims of this study were to describe student’s perception on learning environment, student’s learning approach, relationship between student’s perception on learning environment with learning approach applied in musculoskeletal block at Faculty of Medicine Pelita Harapan University.Method: This research was conducted using mixed method which combines two approaches type. A quantitative approach was the main approach, while qualitative approach acted as facilitatory approach. As many as 106 students of musculoskeletal block participated as sample.Results: Descriptive analysis showed that students perception was good on teaching quality (77.36%), clear goals (59.43%), and learning ability acquired (88.68%). Meanwhile 68.87% of sample had unsatisfied perception on assessment and on workload (73.58%). The correlation of learning environment perception to learning approach revealed p value>0.05 which was not statistically significant. Qualitative findings showed the role of internal motivation in determining learning approach adopted by student. Internal motivation comprised interest in subject, previous knowledge, and self-esteem.Conclusion: Student’s perception of learning environment is not a predictor of learning approach applied by student in musculoskeletal block. Internal motivation take part in determining students’ learning approach.